Synthesis and Biological Activity of Chiral Rho Kinase Inhibitors - Li, Hang; Sun, Changhai; Wang, Xinran; Jiang, Shende; Chen, Ligong; Yan, Xilong (Asian Journal of Chemistry, 2014)
It was found that (S)-6H-1-(5-isoquinolinesulfonyl)-2-hydroxymethyl-1-pyrrolidine and (S)-6H-1-(5- isoquinolinesulfonyl)-2-chloromethyl-1-pyrrolidine displayed excellent Rho inhibitory activity in previous work. Therefore, with these two compounds as lead compounds, we designed and synthesized their enantiomers in order to reveal the effects of chirality on the combination of inhibitor and Rho kinase. Their biological activity evaluation results indicated that the chirality of inhibitors indeed presented important influences on their Rho kinase inhibitory activities. Furthermore, several analogues of the lead compounds were designed and synthesized. It was found that the isostere, (S)-6H-1-(5-isoquinolinesulfonyl)-2-fluorinated-methyl-pyrrolidine (compound 7) exhibited much better Rho kinase inhibitory activity than the lead compounds and strongly promoted synapse formation. Thus, it is believed to be a potential candidate as Rho kinase inhibitors.